EFFECT OF COMPOSITION VARIATION ON CRYSTAL SIZE OF MnO-Fe₂O₃/PS NANOCOMPOSITE LAYER AS SELF CLEANING - Dafri Zaldi; - Ratnawulan (Department of Physics – Universitas Negeri Padang UNP, 2021)
This research is based on the abundance of natural materials such as manganese and iron ore. Manganese is usually used for metal coating and has durability so that it is rich in properties to be used for various purposes in the chemical, pharmaceutical, and technological industries. Meanwhile, iron ore is a stable type of oxide so that it has strong properties and is not easily corroded. This research is a type of experimental research conducted at the Laboratory of Material Physics and Biophysics Faculty of Mathematics and Natural Sciences (FMIPA), Padang State University (UNP), and the Chemistry Laboratory of FMIPA UNP. The tools used are HEM-3D, XRD, and UV-VIS. The precursors were prepared by varying the composition of the ratio of MnO-Fe₂O₃ and PS respectively 0,2:0,2:1 ; 0,4:0,4:1 ; 0,6:0,6:1 ; 0,8:0,8:1 ; 1:1:1. This coating is made by means of the spin coating method and uses a temperature of 60 ° using a oven. The results of this study are the maximum crystal size obtained in MnO is 61.26 nm, Fe₂O₃ is 50.45 nm, and MnO-Fe₂O₃ is 53.08 nm. Also, the maximum% degradation produced is 65.97% in a methyl orange solution, this shows that the MnO-Fe₂O₃/PS layer is well degraded. This degradation ability is known as self cleaning because it is able to break down dirt.